Application of a microfluidics system for the investigation of nanoparticles cellular uptake and development of 3D in vitro models - Oliveira, J. M. (2015)
Microfluidics recently emerged with the potential to fulfill many technological gaps as they possess the ability to produce three-dimensional architectures with controlled spatial relationships between cells, the presence of flow-induced signaling and transduction, and the introduction of chemical gradients necessary to mimic the architecture of the in vivo microenvironment. The integration of tissue engineering (TE) strategies with microfluidic technologies has sparked a breakthrough into the design of in vitro microfluidic culture models that better adapt to morphological changes in tissue structure and function over time, providing a level of precision control that could not be achieved before. Because experiments are run on the micro-scale, small amounts of reagents and cells are needed making it more economic and faster. This technology revolution can be adapted to multiplexed and high throughput assays. These 3D TE in vitro models can potentially comprise multiple tissues and micro-organs obtained by tissue re-cellularization or scaffolding strategies, allowing a deeper understanding of biology processes at multiscales. In the last few years, our group has significantly impact the field of tissue engineering and regenerative medicine by means of strengthening research within the interdisciplinar domains of 3D tissue engineered in vitro models to be used as alternative to animal experimentation and for human health. The developed 3D tissue engineered in vitro models have also possibly investigating nanoparticles internalization by diferent cell types. In conclusion, microfluidics systems show great value in the development of 3D tissue engineered in vitro models mimicking the in vivo conditions, which can accelerate the research achievements in a wide range of fields including neurosciences.